miR‐224‐5p Suppresses Non‐Small Cell Lung Cancer via IL6ST‐Mediated Regulation of the JAK2/STAT3 Pathway - Jiao Tian; Yiming He; Zihui Zhang; Yuxin Zhu; Haixia Ren; Liang Zhang; Lei Li; Wei Li; Weidong Zhang; Ting Xiao; Honggang Zhou; Xiaoping Li (Thoracic Cancer)
ABSTRACT Background Our study aimed to explore the specific functions and potential mechanisms of miR‐224‐5p in non‐small cell lung cancer (NSCLC). Methods We first analyzed the expression of miR‐224‐5p in NSCLC patients and cell lines through the GEO database and qRT‐PCR analysis. Then, we used MTT assays, wound healing assays, Transwell assays, and western blotting to evaluate the effects of miR‐224‐5p on NSCLC cell proliferation, migration, invasion, and epithelial–mesenchymal transition (EMT). Furthermore, we used a xenograft tumor model to evaluate the effect of miR‐224‐5p on NSCLC tumor growth. Potential binding targets of miR‐224‐5p were further identified through the target prediction databases, and the relationships between miR‐224‐5p, its targets, and downstream signaling pathways were further verified using luciferase reporter gene assays and western blotting. Results The GEO database and qRT‐PCR analysis indicated that miR‐224‐5p was significantly downregulated in NSCLC patients and cell lines. Functional assays indicated that inhibiting miR‐224‐5p could enhance the proliferation, migration, invasion, and EMT of NSCLC cells, as well as accelerate tumor growth. In contrast, overexpression of miR‐224‐5p inhibited these processes. We identified IL6ST (interleukin 6 signal transducer) as a binding target of miR‐224‐5p. We observed that miR‐224‐5p could bind to and inhibit IL6ST expression and JAK2/STAT3 signaling pathway, and the inhibition of NSCLC tumor growth and JAK2/STAT3 pathway by miR‐224‐5p could be reversed by IL6ST overexpression. Conclusion Our study demonstrated that miR‐224‐5p inhibited NSCLC by targeting IL6ST, thereby downregulating the JAK2/STAT3 signaling pathway.